Tanggap Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogaea L.) Pada Dosis Pupuk Kalium dan Frekwensi Pembumbunan - Nelson Simanjuntak; Rosita Sipayung; Mariati Mariati (Jurnal Agroekoteknologi, 2014)
Attempts to increase the yield of peanut can be done with fertilizer and pile up. The purpose of thestudy was to determine the response of KCl fertilizer and pile up frequency on the growth and yieldof peanuts. The research was conducted at Pasar I Tanjung Sari street, Medan with the height of 25metres above sea level, began from April until Juli 2013. The design of the research was arandomized block design with two factors. The first factor was dose of KCl fertilizer (0, 50, 100,and 150 kg/ha) and the second was pile up frequency (20; 20 and 40; and 20, 40, and 60 days afterplanted). The parameters observed were plant height, number of branches, flowering age, number ofginofor per sample, number of pods per sample, number of filled pods per sample, weight of podsper plot, weight of grain per plot, and weight of 100 grains. The results showed that the weight ofpods per plot and weight of grain per plot were significantly affected by pile up frequency. Howeverall parameters observed were unsignificantly affected by dose of KCl and treatment interaction.Key words : KCl fertilizer, pile up frequency, peanuts.